Role of Communication and Marital Acceptance in Marital Adjustment for Dual Earners Married under 10 Years - Doho, Saraswati Stefannie; Setiawan, Jenny Lukito (UI Scholars Hub, 2022)
This study aims to determine the role of communication and marital acceptance in marital adjustment for dual earners married under 10 years. A total of 93 respondents are involved in this study. The criteria for selecting respondents are married employees of company X in Surabaya; married under 10 years; have a working spouse. A quantitative research method with a correlational design is used. Communication, marital acceptance, and marital adjustment scales are also used. Multiple linear regression analysis shows that communication and marital acceptance have a significant role in marital adjustment. The contribution of communication and marital acceptance to marital adjustment is 54% (p < 0.05, R2 = 0.540). Thus, communication and marital acceptance predict marital adjustment. This research is expected to be useful for married couples, counselors, and prospective married couples.